Analysis of post-harvest physiological deterioration in cassava transformed with anti-oxidant genes - Nor Hasima Mahmod
Cassava is the sixth most important food crop in the world, where it is the staple food for over 500 million people. Its ability to grow on marginal soil conditions and under minimal care makes cassava a vital 'food security' crop for resource-poor farmers. However, cassava production is constrained by post-harvest physiological deterioration (PPD), a storage root disorder characterised by vascular streaking and discolouration of parenchymal tissue. PPD, which renders the roots unpalatable and unmarketable, leads to significant yield loss in global cassava production. The cause of PPD is not yet fully understood but accumulation of reactive oxygen species (ROS) has been observed in the harvested storage root. It is hypothesised that the ROS, which is triggered by wondering during harvesting, is not modulated due to deficiencies in the ROS-detoxifying systems in cassava roots, causing oxidative stress to occur, which then leads to symptom formation. To investigate this, transgenic cassavas containing five separate anti-oxidant genes were studied-superoxide dismutase (SOD), ascorbate peroxidase (APX), catalase (CAT), gamma glutamyl cysteine synthetase (GCS) and galacturonic acid reductase (GAR). Each gene was controlled bu a root-specific promoter, Patatin, which is also wound-inducible. A high percentage of single-insert lines were recovered, which retained the outward phenotype of WT cassava. While this enable comparative PPD assessment between the transgenics and the WT, this was complicated by the challenge of reproducibly measuring PPD in greenhouse-grown plants. Therefore, a reliable assay to measure PPD in greenhouse-grown samples was developed and a robust method to assess the symptoms with high confidence was devised. Scopoletin, a fluorescent compound was initially tested as an alternative PPD marker but was dismissed as it did not correlate well with PPD symptom development. Overexpression of anti-oxidant genes was observed in selected lines - between 4- to 5-fold increase of relative transcriptional level was achieved in fresh roots and up to 20-fold was achieved in transgenic roots that had been harvested after 24 hours. However, as the increase did not alter the activity of anti-oxidant enzymes, the transgenic cassava plants generally exhibited similar levels of tolerance to oxidative stress and PPD as the WT plants. This result may be partly due to the difficulty of producing sufficient numbers of replicates for analysis, the behaviour of the Patatin promoter in cassava, and the complexity of anti-oxidant responses. Hence, while this thesis has clarified aspects of the PPD response in cassava and the role of anti-oxidant genes in it, it has not been able to identify definitive means to control the problem through altering the expression of individual genes.